Handbook of research on advances and applications in refrigeration systems and technologies - Dinis Gaspar, Pedro, 1974-; Silva, Pedro Dinho da (Advances in mechatronics and mechanical engineering (AMME) book series., 2015)
"This book gathers state-of-the-art research related to thermal performance and energy-efficiency, covering a diverse array of subjects--from the challenges of surface-area frost-formation on evaporators to the carbon footprint of refrigerant chemicals"--